2018
DOI: 10.1063/1.5048010
|View full text |Cite
|
Sign up to set email alerts
|

GaN surface as the source of non-radiative defects in InGaN/GaN quantum wells

Abstract: Blue light-emitting diodes based on III-nitride semiconductors are nowadays widely used for solid-state lighting. They exhibit impressive figures of merit like an internal quantum efficiency close to 100%. This value is intriguing when considering the high dislocation density running throughout the InGaN/GaN quantum well (QW) active region. This striking feature is currently ascribed to carrier localization occurring in the InGaN alloy, which hinders their diffusion toward dislocations. However, it was recentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
110
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(121 citation statements)
references
References 41 publications
10
110
1
Order By: Relevance
“…However, the efficiency of long‐wavelength InGaN devices is hampered by several challenges, one of which is the unintentional incorporation of point defects that act as a source of carrier recombination . Indeed, a number of experimental studies have identified the presence of deep defects in InGaN layers and have alluded to point defects as a source of efficiency reduction in InGaN optoelectronic devices . Identifying the microscopic origin of defects in an InGaN alloy is complicated as the defect levels are likely to exhibit different sensitivities to changes in the In concentration, InGaN bandgap and band edges, and distribution of In and Ga cations.…”
Section: Introductionmentioning
confidence: 99%
“…However, the efficiency of long‐wavelength InGaN devices is hampered by several challenges, one of which is the unintentional incorporation of point defects that act as a source of carrier recombination . Indeed, a number of experimental studies have identified the presence of deep defects in InGaN layers and have alluded to point defects as a source of efficiency reduction in InGaN optoelectronic devices . Identifying the microscopic origin of defects in an InGaN alloy is complicated as the defect levels are likely to exhibit different sensitivities to changes in the In concentration, InGaN bandgap and band edges, and distribution of In and Ga cations.…”
Section: Introductionmentioning
confidence: 99%
“…We study samples with 4 nm-thick single-QWs within p-i-n regions, grown on c-plane bulk GaN substrates by MOCVD; these samples include an InGaN underlayer (UL) beneath the p-i-n region, which improves material quality [10][11][12]. Importantly, the QW is placed at the center of the intrinsic region to avoid modulation-doping, which would alter the recombination dynamics [13].…”
mentioning
confidence: 99%
“…Based on previous studies, point defects such as nitrogen vacancies or surface point defects generated during high temperature growth of GaN layer can be captured by a low-temperature grown InGaN pre-layer [8][9][10] . As a result, the performance of the semi-polar (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) LEDs with the SLS pre-layer can be improved due to a reduction in point defect density.…”
Section: Resultsmentioning
confidence: 99%
“…It is also well-known that it is crucial to insert a single InGaN underlayer or an InGaN/GaN superlattice structure (SLS) as a pre-layer prior to the growth of InGaN/GaN multiple quantum wells (MQWs) as an emitting region in an LED. The performance of the III-nitride LEDs are then dramatically improved [2][3][4][5][6][7][8][9][10] , although the pre-layer is typically grown at a low temperature which generates extra defects [8][9][10] . Furthermore, even for the growth on GaN substrates (where the dislocation density is significantly low), III-nitride LEDs without any pre-layer exhibit much worse performance than those with a pre-layer but grown on sapphire [8][9][10] .…”
mentioning
confidence: 99%
See 1 more Smart Citation